2017
DOI: 10.3390/w9040259
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Precipitation Variability and Trends in the World’s Mediterranean-Climate Areas

Abstract: Abstract:The Mediterranean climate is principally characterized by warm, dry summers and cool, wet winters. However, there are large variations in precipitation dynamics in regions with this climate type. We examined the variability of precipitation within and among Mediterranean-climate areas, and classified the Mediterranean climate as wet, moderate, or dry based on annual precipitation; and strongly, moderately, or weakly seasonal based on percentage of precipitation during summer. Mediterranean biomes are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 65 publications
5
49
0
Order By: Relevance
“…As to what concerns the Mediterranean area, these findings agree with the results of other researchers, who evidenced a clear tendency towards drier conditions of the eastern Mediterranean and negative trends, thus not always significant, in the total rainfall amounts in the western and The results of the present study also confirm past local studies on Europe and Africa, which highlighted relatively large positive trends in the Northern Hemisphere mid-latitudes and high latitudes and a negative one in the subtropics (e.g. New et al 2001;Nouaceur & Mur arescu 2016;Deitch et al 2017). These results also agree with other local studies in the Mediterranean region which evidenced a reduction in precipitation and an increase in the mean and largest dry periods (Nastos & Zerefos 2009;Cindrić et al 2010;S anchez et al 2011;Liuzzo et al 2016;Montaldo & Sarigu 2017).…”
Section: Discussionsupporting
confidence: 93%
“…As to what concerns the Mediterranean area, these findings agree with the results of other researchers, who evidenced a clear tendency towards drier conditions of the eastern Mediterranean and negative trends, thus not always significant, in the total rainfall amounts in the western and The results of the present study also confirm past local studies on Europe and Africa, which highlighted relatively large positive trends in the Northern Hemisphere mid-latitudes and high latitudes and a negative one in the subtropics (e.g. New et al 2001;Nouaceur & Mur arescu 2016;Deitch et al 2017). These results also agree with other local studies in the Mediterranean region which evidenced a reduction in precipitation and an increase in the mean and largest dry periods (Nastos & Zerefos 2009;Cindrić et al 2010;S anchez et al 2011;Liuzzo et al 2016;Montaldo & Sarigu 2017).…”
Section: Discussionsupporting
confidence: 93%
“…At the same time, SOI-/PDO-phase, which is favorable for a north-dry/south-wet California, was only observed in eight winter months. It is consistent with Deitch et al (2017) who reported significantly reduced (increased) precipitation during the past half-century in SoCal (NorCal). This dipole behavior is hypothesized to be contributory to an enhanced long-term trend toward greater aridity in SoCal (Figures 1 and S10).…”
Section: Drought and Climate Change In Californiasupporting
confidence: 91%
“…Moreover, differences in PD, GR and SR consistently identify the east of the region, upward in the Andes mountain ranges, as an area of large changes. This pattern of change, coincides with those reported for Mediterranean-type climate zones worldwide (Ackerly et al, 2014;, where the shifts in the range of climates has been reported to occur poleward and upward and are in agreement with the current trend in climate change within MedCh, where harsher conditions (annual and summer precipitation downward trends) have been identified from 1975 to 2015 (Deitch, Sapundjieff, & Feirer, 2017).…”
Section: Current and Future Patterns Of Biodiversitysupporting
confidence: 91%